PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SMK NEGERI 10 KECAMATAN SUNGAI GELAM KABUPATEN MUARO JAMBI - Pratiwi Indah Sari (Eklektik : Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2018)
The purpose of this research is to know the effect of work environment and work motivation on teacher performance in SMK Negeri 10 Sungai Gelam District Muaro Jambi Regency. The population in the study amounted to 35 teachers. Based on the results of the study, it can be concluded that performance is not solely measured through how a teacher is able to be responsible for the students, but how the teacher is able to dedicate themselves to the development of education in the school. Therefore, factors such as the working environment should receive the attention of all parties involved in advancing the existing education so that the work motivation of teachers can be appreciated in the form of better learning achievement.